Southern Wilt of Geranium - Philip F. Harmon; Carrie L. Harmon; David Norman; Tim Momol (EDIS, 2005)
Southern wilt, caused by the bacterium Ralstonia solanacearum (Rs), is currently an important disease for geranium producers. Different races of R. solanacearum affect hundreds of plant species around the world. This document is PP 206, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date February 2005.